Rational drug repurposing using sscMap analysis in a HOX-TALE model of leukemia - Kettyle, Laura M.J.; Liberante, Fabio G.; Thompson, Alexander (Springer Verlag, 2014)
Drug discovery and development are often hampered by lack of target identification and clinical tractability. Repurposing of approved drugs to life-threatening diseases such as leukemia is emerging as a promising alternative approach. Connectivity mapping systems link approved drugs with disease-related gene signatures. Relevant preclinical models provide essential tools for system validation and proof-of-concept studies. Herein we describe procedures aimed at generating disease-based gene signatures and applying them to established cross-referencing databases of potential candidate drugs. As a proof of principle, we present the identification of Entinostat as a candidate drug for the treatment of HOX TALE-related leukemia.